Art and mental health: Artistic creativity as a therapeutic intervention: Art and mental health - Monteiro, Ilda (2023)
This literature review study has as its main objective the inclusion of art in mental health and consequent improvement through artistic practice. This model intends to use art as a language of emotions, put into practice through a new concept of “therapists” aimed at heterogeneous groups in their limitations and potentialities that contribute to a new concept of therapeutic work that significantly determines the therapy practice. Therapeutic workshops that use artistic activities allow expressiveness, valuing creativity and expressive fantasy, whose foundation focuses on the concept of creation, strengthening self-esteem and the expression of subjectivities. It is in these spaces that subjects are inspired, express themselves and conceive new languages, new ways of relating, new places of existence and new ways of existing in the world. Therapeutic work with artistic expressions favors the biopsychosocial recovery of people with mental health problems, as it supports clinical treatment through the creative experience in which the social integration of people with mental health problems will be more effective with the respective improvement of inclusion, without the need to create mechanisms of social segregation. Through art, all subjects develop their relational and emotional skills, create mechanisms of defense and belonging in a society where there is no place for artists to survive, but for everyone to live in a concept of complementarity.